Avaliação de desempenho de pessoas em bancos: uma análise de políticas, práticas e abordagens - Aranha , Rodrigo Octavio Macedo (2010)
This is a study in the field of Human Resources Management and deals with the subject of people performance evaluation. The main purpose of this study was to investigate the policies and practices of Human Resources used by banks in Brazil in their processes of performance evaluation and to analyze how and why the dimensions of performance, such as results, behavior, development and potential, are identified and measured in these organizations. A secondary objective was to identify how the people management decisions are taken by these organizations based on their processes of performance evaluation.